Islamic Capital Market Integration in 5 ASEAN Countries in the Covid-19 Era - Muhammad Ryan Romadhon; Siti Mutmainah (Jurnal Ekonomi Syariah Teori dan Terapan, 2023)
ABSTRACT The purpose of this study was to analyze the short-term and long-term relationship between the Islamic capital markets of 5 selected countries in the Covid-19 era. This study used a quantitative approach using weekly secondary data from January 2020 to December 2022. The data analysis model used Vector Auto Regression (VAR) analysis. The results of this study show that in the short term, variants in the capital market will change due to shocks in other ASEAN Islamic capital markets, but short-term deviations in the Islamic capital market will adjust in the long term. meanwhile, in the long run, Islamic capital markets in ASEAN countries that were tested, have integrated despite the occurrence of a health crisis that also has an impact on the financial crisis. This provides an opportunity for investors to mitigate risks and increase profit margins, especially in Islamic stock exchanges in ASEAN countries. On the other hand, this research allows investors to reformulate a more diversified portfolio after the Covid-19 pandemic. Keywords: Integration, Islamic Capital Market, ASEAN, Covid 19 ABSTRAK Tujuan dari penelitian ini adalah untuk menganalisis hubungan jangka pendek dan jangka panjang antara pasar modal syariah 5 negara terpilih di era Covid-19. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan data sekunder mingguan januari 2020 sampai dengan desember 2022. Model analisis data menggunakan analisis Vector Auto Regression (VAR). Hasil penelitian ini menunjukkan bahwa dalam jangka pendek, varian di pasar modal akan berubah karena guncangan di pasar modal syariah ASEAN lainnya, namun penyimpangan jangka pendek di pasar modal syariah akan menyesuaikan dalam jangka panjang. sementara dalam jangka panjang, pasar modal syariah di negara-negara ASEAN yang teruji, memiliki integrasi meskipun terjadi krisis kesehatan yang juga berdampak pada krisis keuangan. Hal ini memberikan suatu kesempatan bagi para investor untuk memitigasi risiko dan memperbesar margin keuntungan terutama di bursa saham syariah negara ASEAN. Disisi lain, dengan adanya penelitian ini memungkinkan membantu para investor untuk merumuskan kembali portofolio yang lebih terdiversifikasi setelah terjadinya pandemi covid-19. Kata Kunci: Integrasi, Pasar Modal Syariah, ASEAN, Covid 19 REFERENCES Abd. Majid, M. S. (2018). Who Co-Moves The Islamic Stock Market of Indonesia -The US, The UK, or Japan? Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 10(2), 267–284. doi:10.15408/aiq.v10i2.7288 Abdul Karim, B., & Abdul-Rahman, A. (2020). Market integration in asean-5: Evidence of Islamic and conventional stock markets. Polish Journal of Management Studies, 21(1), 186–198. doi:10.17512/pjms.2020.21.1.14 Abdulkarim, F. M., Akinlaso, M. I., Hamid, B. A., & Ali, H. S. (2020). The nexus between oil price and Islamic stock markets in Africa: A wavelet and Multivariate-GARCH approach. Borsa Istanbul Review, 20(2), 108–120. doi:10.1016/j.bir.2019.11.001 Ahmed, F. (2021). Assessment of Capital Market Efficiency in COVID-19. European Journal of Business and Management Research, 6(3), 42–46. doi:10.24018/ejbmr.2021.6.3.839 Awwal, M. A. F. (2021). The corona pandemic on sharia capital market in Indonesia. Iqtishoduna, 10(2), 95–104. doi:10.36835/iqtishoduna.v10i2.864 Aziz, A., Rachmat, N., Abu, A., Adnan, Y., Islam, M. H., Islam, U., Hasan, Z., & Indonesia, G. (2020). Does integration superpower stock market for index of sharia stock in Indonesia. International Journal of Management Science and Business Research, 9(10), 170–177. doi:10.5281/zenodo.4990752 Bekaert, G., Harvey, C. R., & Ng, A. (2005). Market integtation and cintagration. The Journal of Business, 78(1), 39-70. doi:10.1086/426519 Cahyaningrum, A., & Robiyanto, R. (2021). Pengujian integrasi pasar modal di Kawasan Asia sebelum dan selama pandemi Covid-19. Jurnal Akuntansi Keuangan Dan Bisnis, 14(2), 211–220. doi:10.35143/jakb.v14i2.4673 Chen, M. P., Lee, C. C., Lin, Y. H., & Chen, W. Y. (2018). Did the S.A.R.S. epidemic weaken the integration of Asian stock markets? Evidence from smooth time-varying cointegration analysis. Economic Research, 31(1), 908–926. doi:10.1080/1331677X.2018.1456354 Chen, N. F., Roll, R., & Ross, S. A. (1986). Economic Forces and the Stock Market. Journal of Bussiness, 59(3), 383–403. Climent, F., & Meneu, V. (2003). Has 1997 Asian crisis increased information flows between international markets. International Review of Economics & Finance, 12(1), 111–143. doi:10.1016/s1059-0560(02)00140-5 Dantes, R. (2019). Wawasan pasar modal syariah. Ponorogo: Wade Group. Elmizan, G. H., Rahmawati, V., & Talim, A. (2022). Understanding and interest in sharia capital market investment of PTKIN and PTKIS Students. Indonesisan Interdisciplinary Journal of Sharia Economics, 5(2), 441–458. doi:10.31538/iijse.v5i2.2165 Erdo, S., Gedikli, A., & Ismail, E. (2020). Volatility spillover effects between Islamic stock markets and exchange rates"¯: Evidence from three emerging countries. Borsa Istanbul Review, 20(4), 322-333. doi:10.1016/j.bir.2020.04.003 Fama, E. F. (1970). Efficient capital markets: A review of theory and empirical Work. The Journal of Finance, 25(2), 383–417. doi:10.2307/2325486 Fathoni, H., & Sakinah, G. (2021). Peran pasar modal syariah dalam laju pertumbuhan ekonomi di Indonesia. Khazanah Multidisiplin, 2(1), 33–44. Gujarati, D. N., & Porter, D. C. (2009). Basic econometrics. New York: McGraw-Hill Companies,Inc. Gunawan, D., & Cahyadi, W. (2019). Integrasi pasar saham Indonesia dengan Pasar Saham Asia. Jurnal PasarModal Dan Bisnis, 1(2), 145–154. doi:10.37194/jpmb.v1i2.27 Handini, S., & Astawinetu, E. D. (2020). Teori portofolio dan pasar modal Indonesia. Surabaya: Scopindo Media Pustaka. Hartati, N. (2021). Investasi saham syariah di bursa efek Indonesia dalam perspektif hukum ekonomi syariah. J-HES (Jurnal Hukum Ekonomi Syariah), 5(1), 33–48. doi:10.26618/j-hes.v5i01.4819. Karim, B. A., & Karim, Z. A. (2012). Integration of ASEAN-5 stock markets: A revisit. Asian Academy of Management Journal of Accounting and Finance, 8(2), 21–41. Khan, K., Zhao, H., Zhang, H., Yang, H., Shah, M. H., & Jahanger, A. (2020). The impact of COVID-19 pandemic on stock markets: An empirical analysis of world major stock indices. Journal of Asian Finance Economics and Business, 7(7), 463–474. doi:10.13106/jafeb.2020.vol7.no7.463 Laopodis, N. T. (2020). Understanding investments (2nd Edition). London: Routledge. Liu, H., Manzoor, A., Wang, C., Zhang, L., & Manzoor, Z. (2020). The COVID-19 outbreak and affected countries stock markets response. International Journal of Environmental Research and Public Health, 17(8), 1–19. doi:10.3390/ijerph17082800 Majid, M. S. A., Meera, A. K. M., & Omar, M. A. (2008). Interdependence of asean-5 stock markets from the US and Japan. Global Economic Review, 37(2), 201–225. doi:10.1080/12265080802021201 Malik, A. D. (2017). Analisa faktor – faktor yang mempengaruhi minat masyarakat berinvestasi di pasar modal syariah melalui Bursa Galeri Investasi Uisi. JEBIS: Jurnal Ekonomi Dan Bisnis Islam, 3(1), 61-84. doi:10.20473/jebis.v3i1.4693 Mustapha, M. I., Bacha, O. I., & Masih, M. (2017). Dynamics of islamic stock market returns and exchange rate movements in the ASEAN Countries in a regime-switching environment"¯: Implications for the islamic investors and risk hedgers. Munich Personal RePEc Archive: University Library of Munich, 82218. Noptriyani, I., Ahmadsyah, I., & Aufa, S. (2016). Faktor-Faktor yang menjadi penghambat bagi mahasiswa dalam memiliki investasi (Studi kasus pada mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Ar-Raniry). Global Journal of Islamic Banking and Finance, 2(1), 82–109. doi:10.22373/jihbiz.v2i1.8580 Nurlina., Abubakar, A., & Khalid, R. (2022). Investasi perspektif Al-Qur'an (Studi menggunakan metode Maudhu'i). E-QIEN: Jurnal Ekonomi dan Bisnis, 11(1), 997–1004. doi:10.34308/eqien.v11i1.832 Oceania, F. G., & Ardiansyah, M. (2023). Dampak shock pada indeks saham syariah global dan indeks saham syariah Regional Asean terhadap perubahan harga saham pada Jakarta Islamic Index Periode 2020-2022 2(03). (Thesis Magister, Universitas Islam Negeri Sunan Kali Jaga) https://digilib.uin-suka.ac.id/id/eprint/55880/ Pajar, R. C., & Pustikaningsih, A. (2017). Pengaruh Motivasi Investasi Dan Pengetahuan Investasi Terhadap Minat Investasi Di Pasar Modal Pada Mahasiswa Fe Uny. Profita: Kajian Ilmu Akuntansi, 5(1), 1–16. Pardal, P., Dias, R., Suler, P., Teixeira, N., & Krulicky, T. (2020). Integration in Central European capital markets in the context of the global COVID-19 pandemic. Equlibrium: Quarterly Journal of Economics and Economic Policy, 15(4), 627-650. doi:10.24136/eq.2020.027 Peristiwo, H. (2016). Analisis minat investor di kota Serang terhadap investasi syariah pada pasar modal syariah. Jurnal Ekonomi Keuangan dan Bisnis Islam, 7(1), 37–52. doi:10.32678/ijei.v7i1.7 Prasetyo, T. A. (2022). Analisis indeks harga saham syariah internasional dan variabel makro ekonomi terhadap Jakarta Islamic Index. At Tawazun, 10(01), 41–53. Qizam, I., Ardiansyah, M., & Qoyum, A. (2020). Integration of Islamic capital market in ASEAN-5 countries: Preliminary evidence for broader benefits from the post-global financial crisis. Journal of Islamic Accounting and Business Research, 11(4), 811–825. doi:10.1108/JIABR-08-2019-0149 Rabbani, I. A., & Saputra, I. (2022). Financial literacy dan overconfidence dalam keputusan investasi. Journal of International Management, 1(1),1–18. Romadhon, M. R., & Ardiansyah, M. (2022). Analisis Pasar Modal Syariah 5 Negara ASEAN di Era Pandemi. E-Journal Ekonomi Bisnis dan Akuntansi Universitas Jember, 9(1), 36–41. doi:10.19184/ejeba.v9i1.30412 Saiti, B. (2015). Cointegration of Islamic stock indices: Evidence from five ASEAN countries. International Journal of Scientific & Engineering Research. 6(7), 1392–1405. Sims, C. A. (1972). Money, income, causality. The American Economic Review, 62(4), 540–552. Siregar, P. A., Sari, S., & Batubara, M. (2022). Perspektif perkembangan dan tantangan pasar modal di Indonesia. Economic Reviews Journal, 2(1), 923–926. Sn, A., & Rahayu, S. E. (2022). Pengaruh indeks saham syariah Jepang (Djijp) dan inseks saham syariah Malaysia (Djmy25d) terhadap indeks saham syariah Indonesia (Issi). Point: Jurnal Ekonomi & Manajemen, 4(1), 53–66. Storey, I., & Choong, W. (2022). Russia's invasion of ukraine"¯: Southeast Asian responses and why the conflict matters to the region. ISEAS Yusof IShak Institute, 24, 1–13. Sugiyono. (2013). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta. Sulistiana, I., Hidayati, & Sumar. (2017). Model vector auto regression (Var) and vector error correction model (Vecm) approach for inflation relations analysis, gross regional domestic product (Gdp), world tin price, Bi rate and Rupiah exchange rate. Integrated Journal of Business and Economics, 1(2), 17–32. doi:10.5281/zenodo.1147673 Suteja, J., & Gunardi, A. (2016). Manajemen investasi dan portofolio (Edisi Kesatu). Bandung: PT Refika Aditama. Tiwang, R. A., Karamoy, H., & Maramis, J. (2020). Analisis integrasi pasar modal Indonesia dengan pasar modal global (Nyse, Sse, Lse, dan Pse). JMBI UNSRAT: Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi, 7(3), 657–684. doi:10.35794/jmbi.v7i3.31442 Walewangko, E., Saerang, I. S., & Maramis, J. B. (2018). Analisi integrasi saham bursa efek Indonesia dan beberapa bursa efek Negara ASEAN periode Januari 2016 - Juni 2018. Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 6(4), 3923–3932. doi:10.35794/emba.v6i4.21917 Waworundeng, J. H., & Rate, P. Van. (2018). Analisis hubungan pasar modal ASEAN dengan pasar modal Indonesia di Bursa Efek Indonesia. Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis Dan Akuntansi, 6(1), 271–280. doi:10.35794/emba.v6i1.19049 Widarjono, A. (2018). Ekonometrika: Pengantar dan aplikasinya disertai Panduan Eviews (5th Edition). Yogyakarta: UPP STIM YKPN.